Inovasi Pendidikan dalam Proses Pembelajaran di SMAN 1 Kota Kupang Pasca Covid-19 - Padabain, Firmanto; Lopez, Christin Moru; Zogara, Kezia Sheryl Victoria; Pradana, I Putu Yoga Bumi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
This study aims to describe various educational innovations in the learning process at SMAN 1 Kupang in the post-Covid-19 period and the factors that influence the process of innovation. This study uses qualitative methods with the type of case study research, with interview techniques. This research was sourced from 7 informants who were directly involved in the process of educational innovation in the learning process at SMAN 1 Kota Kupang. This study found that digital learning innovations had been carried out by schools before the Covid-19 period took place. This innovation was then developed by the school principal and teachers when Covid-19 occurred and continued after post-Covid-19. This is following the aim of SMAN 1 Kota Kupang to become a technology-based school and a driving school in the City of Kupang.